Impact of Thrombopoietin Receptor Agonists on Pathophysiology of Pediatric Immune Thrombocytopenia - Paschalis Evangelidis; Konstantinos Tragiannidis; Eleni Gavriilaki; Athanasios Tragiannidis (Current Issues in Molecular Biology)
Immune thrombocytopenia (ITP) in pediatric patients is a common cause of isolated thrombocytopenia. Various pathophysiological mechanisms are implicated in ITP pathogenesis, including the production of autoantibodies against components of platelets (PLTs) by B-cells, the activation of the complement system, phagocytosis by macrophages mediated by Fcγ receptors, the dysregulation of T cells, and reduced bone marrow megakaryopoiesis. ITP is commonly manifested with skin and mucosal bleeding, and it is a diagnosis of exclusion. In some ITP cases, the disease is self-limiting, and treatment is not required, but chronic-persistent disease can also be developed. In these cases, anti-CD20 monoclonal antibodies, such as rituximab and thrombopoietin (TPO) receptor agonists, can be used. TPO agonists have become standard of care today. It has been reported in the published literature that the efficacy of TPO-RAs can be up to 80% in the achievement of several end goals, such as PLT counts. In the current literature review, the data regarding the impact of TPO agonists in the pathogenesis of ITP and treatment outcomes of the patients are examined. In the era of precision medicine, targeted and individualized therapies are crucial to achieving better outcomes for pediatric patients with ITP, especially when chronic refractory disease is developed.